2013
DOI: 10.1084/jem.20130212
|View full text |Cite
|
Sign up to set email alerts
|

Immune history shapes specificity of pandemic H1N1 influenza antibody responses

Abstract: The specificity of H1N1 antibody responses can be shifted to epitopes near the HA receptor–binding domain after sequential infections with viral strains that share homology in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
197
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(212 citation statements)
references
References 29 publications
15
197
0
Order By: Relevance
“…The results of our detailed clonal analysis extend two recent serological studies of the human antibody response to the H1N1pdm09 virus (14,37). Li et al have shown that human individuals born between 1983 and 1996 (after donor H), who were exposed in early life to former seasonal H1 viruses that retained K130, narrowly focused their antibody response on this region on exposure to H1N1pdm09 (37).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of our detailed clonal analysis extend two recent serological studies of the human antibody response to the H1N1pdm09 virus (14,37). Li et al have shown that human individuals born between 1983 and 1996 (after donor H), who were exposed in early life to former seasonal H1 viruses that retained K130, narrowly focused their antibody response on this region on exposure to H1N1pdm09 (37).…”
Section: Discussionsupporting
confidence: 79%
“…Mice were weighed and scored according to previously described criteria (65), and mice with 20% weight loss or morbid clinical scores were humanely killed. (14,37). The importance of this distinction lies in the fact that the 2013-2014 H1N1 viruses, which were not detected as drifted in the standard analysis with ferret sera, have been associated with severe infections in middle-aged and elderly humans previously shown to be relatively protected (63).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The haemagglutination inhibition (HI) titre is associated with the level of protection [3,4] against a given strain. However, as influenza epidemiological studies adopt a 'life course view' to the immune response, it has become apparent that interpretation of HI titre should be done within the context of the timing, order, and antigenic similarity of the viral strains to which an individual is exposed [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%